In vitro activity of aztreonam-avibactam against carbapenem-resistant Pseudomonas aeruginosa from Southern Brazil - Gabriela da Silva Collar; Natália Kehl Moreira; Patrícia Orlandi Barth; Maria do Carmo Fontourac Pereira; Afonso Luís Barth; Juliana Caierão (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Abstract Carbapenem-resistant Pseudomonas aeruginosa (CR-PA) has limited therapeutic options, particularly when metallo-β-lactamases are present. We evaluated aztreonam-avibactam (AZA) against 48 clinical P. aeruginosa isolates, including 44 CR-PA with 18 difficult-to-treat resistant isolates. Class B carbapenemase genes were present in 50.0%, mainly bla NDM−1 . AZA MICs ranged from ≤ 0.5 to > 256 µg/mL (MIC50/90, 16/64 µg/mL), and 58.3% of isolates had AZA MICs ≤ 16 µg/mL. Among aztreonam-resistant isolates, AZA restored susceptibility in 33.3%, less frequently than aztreonam plus ceftazidime-avibactam (63.0%).